Effect of Carbon Fiber Rod Reinforcement on Slurry Erosive Behavior of Al6061 Composites. (2016) - Adarsha, H.; Keshavamurthy, R.; Ramesh, S.; Noronha, Naveen P.
Abstract: Continuous carbon fiber rod reinforced Al6061 composites were fabricated by liquid metallurgy technique. Micro-structure and slurry erosion studies were carried out on the developed composites. The influence of experimental parameters such as slurry particle size, slurry concentration and spindle rotational speed on slurry erosive wear behavior of the developed composites have been studied. The developed composites have shown an improvement in slurry wear resistance properties when compared to the matrix alloy. The worn surfaces and the slurry particles were observed using a scanning electron microscope to validate the wear mechanism.